Disscussion on the Design Philosophy to Meet Water Consumption Index of Circulation Cooling Combined-Cycle Peak-Regulation Power Plant in South China - ZHANG Ying; ZHANG Guogang; ZOU Jian (南方能源建设, 2022)
[Introduction] With the promotion of comprehensive utilization of natural gas and the encouragement of clean energy power generation, the construction of large combined-cycle power plant is one of the important forms to achieve this goal. [Method] In this paper, through case study, scheme formulation, analysis and summary, the design philosophy to meet water consumption index of large combined-cycle peak-regulation power plant in south China was studied and discussed: The water source characteristics and design difficulties of the project were analyzed, the water-saving design scheme was formulated, the water balance was calculated, and other water-saving design ideas were discussed. [Result] In order to meet the increasingly stringent requirements of water consumption index, large circulation cooling combined-cycle peak-regulation power plant in South China should consider the water source characteristics, selection of concentration ratio of cooling tower and reuse of cooling tower discharge water based on the site conditions of the project, and formulate appropriate design schemes to ensure the realization of water-saving goal. [Conclusion] The research can provide design philosophy for the same type plants to meet water comsuption index.